PC.87 Initiating a Specialist Respiratory Service for Neonates with Chronic Lung Disease. (9th June 2014) - Batey, N; Dorling, J; Bhatt, J
Abstract : Background: Despite advances in neonatal care some preterm infants still require home oxygen. In our tertiary neonatal service there was a transition with the management of infants with chronic lung disease requiring oxygen at discharge moving to Paediatric Respiratory led care. Our hypothesis was a formalised home oxygen service with a structured monitoring and weaning programme would reduce the length of time spent in oxygen and the number of hospital readmissions. Method: We retrospectively identified two cohorts of preterm neonates requiring home oxygen. The first cohort received care led by the neonatal team and the second the respiratory team. The first cohort were discharged between January 2004–December 2006 and the second between January 2008–December 2010. Demographic, hospital readmission and home oxygen data were collected from hospital based computer systems and clinical notes. Results: Conclusions: Provision of the service has led to a greater number infants being discharged in oxygen but a shorter duration of oxygen therapy. In our experience the increase in neonates requiring home oxygen is likely to be secondary to shorter neonatal stays, increased awareness and provision of oxygen saturation sleep studies prior to discharge However, the structured monitoring and weaning programme led to a shorter duration of home oxygen therapy and fewer children requiring readmission.